Pengaruh Faktor Persepsi Dan Sikap Konsumen Terhadap Keputusan Pembelian Rokok Mild Di Kecamatan Banda Sakti Kota Lhokseumawe - Teuku Edyansyah; Juni Ahyar (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
The purpose of this study was to analyze the effect of consumer perceptions and attitudes on purchasing decisions for Mild cigarettes in Banda Sakti District, Lhokseumawe City. The population in this study is the community in the Banda Sakti District, Lhokseumawe City, amounting to 75226, using the Slovin formula, the sample size is 100 respondents. Data were analyzed using multiple linear regression analysis. From the results of the study, the Adjusted R2 value of 0.669 means that consumer perceptions (X1) and consumer attitudes (X2) affect purchasing decisions (Y) by 0.669 or 66.9% and the remaining 33.1% is influenced by other factors outside this research model. . Based on the partial test, consumer perceptions (X1), consumer attitudes (X2) have a significant effect on purchasing decisions (Y). Simultaneous testing, the value of Fcount (101.109) > Ftable (2.70) means that simultaneously consumer perceptions (X1) and consumer attitudes (X2) have a significant effect on purchasing decisions (Y) Mild cigarettes in Banda Sakti District, Lhokseumawe City. Keywords: Consumer Perception, Consumer Attitude, Purchase Decision